“Stress Role Overload Model” towards Work Family Conflict and Teachers Performance - Dyah Perwita; Rio Dhani Laksana; Viviana Mayasari (Jurnal Lingua Idea, 2020)
This research was conducted to determine the factors that affect the stress role overload that occurs in women teachers who have experienced work family conflict and impact on the performance of teachers in school. Data collection is done empirically through teachers in some of the state high School of Banyumas and Banjarnegara district. The research approach used is a quantitative approach. Data collection conducted with survey questionnaire and purposive sampling method. The sample criteria is (1) The respondent must be married, (2) The respondent has a child, (3) is a dual career pair/have a partner who also works. The result of the spread of sample questionnaire that deserves to be processed and analysis amounted to 134 respondents. The research approach utilizes an in-role-performance approach and an extra-role-performance testing Model and hypothesis using the Structural Equation Model (SEM) equation analysis technique. The results showed that role overload has positive effect on teacher performance, family support has positive effect on teacher performance, teacher certification positively affects teacher performance and work family conflict does not affect in-role-performance or extra-role-performance.